Adaptive Transformation Model of Traditional Islamic Educational Institutions in Indonesia: An Integrative Analysis of Pesantren, Mosques, Surau, and Meunasah - Nahdliyatul Mufidah; Amir Maliki Abitolkha; Viki Mayanfauki (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: Adaptive Transformation Model of Traditional Islamic Educational Institutions in Indonesia: An Integrative Analysis of Pesantren, Mosques, Surau, and Meunasah Objective: This study examines the adaptive transformation and contributions of traditional Islamic educational institutions, such as pesantren, mosques, surau, and meunasah, within Indonesia's national education system. Methods: A qualitative approach using Qualitative Content Analysis (QCA) was employed to analyze peer reviewed journal articles, policy documents, regulations, and relevant literature. Data were analyzed through systematic coding, categorization, interpretation, and thematic synthesis to develop a conceptual model. Results: Four transformational dimensions were identified: Tradition, Adaptation, Integration, and National Contribution. These institutions have successfully preserved their Islamic identity and local wisdom while adapting to the demands of contemporary education. Conclusion: Their transformation reflects the integration of Islamic values, local culture, and national education policies without compromising their institutional identity. Contribution: This study proposes the Adaptive Transformation Model of Traditional Islamic Educational Institutions as a novel conceptual framework to support the development of inclusive, adaptive, and sustainable Islamic education policies.INDONESIAN: Transformasi dan Kontribusi Lembaga Pendidikan Islam Tradisional di Indonesia: Studi Integratif atas Pesantren, Masjid, Surau dan MeunasahTujuan: Penelitian ini bertujuan menganalisis transformasi adaptif dan kontribusi lembaga pendidikan Islam tradisional, yaitu pesantren, masjid, surau, dan meunasah, dalam sistem pendidikan nasional Indonesia. Metode: Penelitian menggunakan pendekatan kualitatif dengan metode Qualitative Content Analysis (QCA) terhadap artikel jurnal bereputasi, dokumen kebijakan, regulasi, dan literatur yang relevan. Analisis dilakukan melalui tahapan pengodean, kategorisasi, interpretasi, dan sintesis tematik untuk membangun model konseptual. Hasil: Penelitian mengidentifikasi empat dimensi transformasi, yaitu Tradisi, Adaptasi, Integrasi, dan Kontribusi Nasional. Keempat lembaga mampu mempertahankan identitas keislaman dan kearifan lokal sekaligus beradaptasi dengan tuntutan pendidikan modern. Kesimpulan: Transformasi berlangsung secara adaptif melalui integrasi nilai-nilai Islam, budaya lokal, dan kebijakan pendidikan nasional tanpa menghilangkan identitas kelembagaan. Kontribusi: Penelitian ini menawarkan Model Transformasi Adaptif Lembaga Pendidikan Islam Tradisional sebagai kebaruan konseptual yang menjadi rujukan bagi pengembangan kebijakan pendidikan Islam yang inklusif, adaptif, dan berkelanjutan.